The Tax Implications of Teaching Overseas - Rolfe, Robert J.; Doupnik, Timothy S. (Journal of International Business Studies, 1986)
Teaching in another country can have tax advantages both for U.S. professors teaching overseas and for our foreign professors teaching in the United States. This paper examines relevant tax law and treaty provisions that can exempt teaching income from taxation or permit certain living expenses to be deducted. With careful planning, professors may be able to shield up to two years of income from taxation.